Spectrophotometric Determination of Valdecoxib from Bulk Drug and Formulation - Baviskar, D.T.; Jagdale, S.C.; Girase, N.O.; Deshpande, A.Y.; Jain, D.K. (Asian Journal of Chemistry, 2010)
The present method was used for bulk form as well as the formulation of the valdecoxib and was expanded to study dissolution profile of valdecoxib tablets. The measurements were done at 241 nm, linear concentration range was observed to be 3-17 μg/mL. In the UV method, the percentage recovery was found to be between 99.52-100.32. The dissolution studies indicate that the method can be used for the development of formulations. The low values of the standard deviation and % coefficient of variation also confirms the accuracy and suitability of the method.